DIGLOSSIA IN MANDAILINGESE WEDDING CEREMONIES (THE MARKHOBAR BORU MOMENT IN SOUTH PANYABUNGAN) - Sirait, Resdilla (Journal of English Education and Linguistics, 2023)
This study aims to find out whether diglossia is found in the Mandailing language, especially in markhobar weddings, marriage is a physical and spiritual bond between a man and a woman as a man and a woman, the goal of which is to form a happy and healthy family (family). Eternal life based on faith in God Almighty. In the context of Mandailing culture, Markhobar can be interpreted as a formal utterance delivered in a traditional Mandailing ceremony; and in siriaon (partying in a happy mood) and in silulutun (partying in a sad mood). Standards passed down from generation to generation, markhobar has procedures agreed upon with the Mandailing people. There is diglossia in everyday Mandailing with the language used in markhobar events. According to interviews conducted, diglossia in Mandailing is quite significant, as the word donok has changed to become more official, namely sisolkot which means "close" in Indonesian. This research on diglossia in the Mandailing language is very useful in helping people to differentiate between formal and informal language in Mandailing.